Editorial: Perspectivas discursivas da divulgação/popularização da ciência - Grillo, Sheila Vieira de Camargo; Giering, Maria Eduarda; Motta-Roth, Désirée (Bakhtiniana. Revista de Estudos do Discurso, 2016)
Editorial